The Relationship Between Self-Regulated Learning and Demographic Characteristics Among Undergraduate Nursing Students - Salsabila, Khairunnisa Vania; Widianti, Efri; Permana, Ryan Hara (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Self-regulated learning is the ability of individuals to actively regulate thought, feeling, and behavior during the learning process to achieve academic goals. Self-regulated learning is important to support the academic success of nursing students, but there is a lot of literature showing that nursing students are faced with various problems in learning such as tight assignment deadlines, time management, too many assignments, and difficulties in understanding the material caused by not being able to control and regulate themselves during the learning process. Objective: The purpose of this study was to determine the relationship between self-regulated learning and the demographic characteristics of nursing students. Methods: This study was a descriptive quantitative with cross sectional approach. The sample in this study is 276 respondents using a proportionate stratified random sampling technique. Self-Regulated Online Learning Questionnaire (SOL-Q) is used to measure the level of self-regulated learning. Results: The result of this study showed that there is a relationship between self-regulated learning and college years (p 0.05). Conclusion: Final year students who have low self-regulated learning can be caused by a lack of ability to manage time and motivation, while first-year students have high enthusiasm and motivation to succeed in academic fields. Students need to pay attention and have supporting factors in order to have good self-regulated learning The faculty is expected to be able to provide programs that help students develop self-regulated learning skills.